Meningkatkan Kemampuan Mengungkapkan Bahasa melalui Kegiatan Bermain pada Anak Kelompok Bermain Kristen Citra Bangsa - Novilia Devi Dewitanty; Selviana Yosefa Sabu Balun (Early Childhood Education Development and Studies (ECEDS), 2021)
The development of language is a highly important process as language is a lifelong process that bagins from birth. The primary function of language is communication. How ever in the kristen citra bangsa playgroup, the writer found that the childrens ability to exprres themselves in language is underdevekoped. Many children remind silent, nod, or shake their heads when communication with the teacher in the classroom. The puurpose of this research is to enhance the children language expression abilities through play activities. This study employs a classroom action research aprroach conducted in two cycles. The research subjects are six children in the kristen citra bangsa playgroup. Data collection techniques include observation, assignments and documentation. The obtained results indicate that in the precycles, the childrens abilities met the expected level only at 16,7% in cycle 1, this increased to 50%, and in cycle 2, further improved to 83 %. In conclusion, through classroom play activities, childrens language exprresion abilities develop significantly.